BIOECOLOGICAL EXPLORATION AND DISTRIBUTION MAPPING OF CYPRINIDAE FISH IN THE BATANG ASAI RIVER, SAROLANGUN, JAMBI PROVINCE - Yoppie Wulanda; Rizky Janatul Magwa; Ester Restiana Endang Gelis; Septy Heltria; Lauura Hermala Yunita; Farhan Ramdhani; Febrina Rolin; Yusyam Leni; Muhammad Hafidz Ibnu Khaldun; Ainun Rohmawati Bareta (Universitas Mataram, 2026)
The Batang Asai River in Sarolangun Regency, Jambi, is one of the major rivers with a length of approximately 104 km. Currently, its water quality is declining due to anthropogenic activities such as land clearing, settlements, and mining. This condition threatens the sustainability of fish populations, particularly those from the Cyprinidae family, which are important food fish and sensitive to environmental degradation. However, scientific information regarding the bioecology and spatial distribution of Cyprinidae in this area remains very limited. Therefore, this study is necessary to provide baseline data to support adaptive conservation strategies and fisheries management. The objectives of this research are to identify Cyprinidae species, analyze bioecological aspects (morphometrics, diversity, reproduction, and habitat characteristics), map spatial distribution based on GIS, and determine conservation status according to the IUCN Red List. The study was conducted in August 2025 at three observation stations. The methods used include field surveys, bioecological analysis, and GIS-based spatial mapping. The results showed that 19 species of Cyprinidae were identified with a total of 482 individuals. The fish diversity index value of 2.07 indicates a moderate diversity category, with an evenness value of 0.70 and a dominance value of 0.17. The sex ratio of males to females was 1.9:1, dominated by fish at gonadal maturity stage (GMS) I with 263 individuals. In general, the water quality of the Batang Asai River still supports fish life, and no species were classified as threatened according to the IUCN Red List.